Diagnosis and follow-up of monoclonal gammopathies of undetermined significance; information for referring physicians. (September 2013) - Caers, Jo; Vekemans, Marie-Christiane; Bries, Greet; Beel, Karolien; Delrieu, Vanessa; Deweweire, Anne; Demuynck, Hilde; De Prijck, Bernard; De Samblanx, Hadewijch; Kentos, Alain; Meuleman, Nathalie; Mineur, Philippe; et al.
Abstract The prevalence of monoclonal gammopathy of undetermined significance (MGUS) is generally estimated at 3.4% in the general population over 50 years, and its incidence increases with age. MGUS represents a preneoplastic entity that can transform into multiple myeloma or other lymphoproliferative disorders. The risk of malignant transformation is estimated at 1% per year and persists over time. Predictors of malignant transformation have been identified such as the heavy chain isotype, The level of monoclonal proteins, increasing levels of the monoclonal component during the first years off follow-up, the percentage of bone marrow plasmocytosis, the dosage of serum free light chains, the presence of immunophenotypically abnormal plasma cells, aneuploidy, and the presence of circulating plasma cells. Prognostic scores that combine certain of these factors have been proposed and allow the identification of high-risk patients. Their use could assist in tailoring the care for each patient, based on his/her risk profile.